Jorge el curioso - Rey, H. A. (Hans Augusto), 1898-1977 (Boston : Houghton Mifflin, 1990)
The curiosity of a newly-captured monkey gets him into continual trouble.
460
Accelerated Reader
Keywords: Monkeys -- Juvenile fiction; Monos -- Novela juvenil